Comparison of intracytoplasmic sperm injection with testicular spermatozoa success in infertile men with obstructive and non-obstructive azoospermia; a retrospective analysis. (3rd July 2017) - Yalcin, Ibrahim; Berker, Bulent; Sukur, Yavuz Emre; Kahraman, Korhan; Ates, Can
Abstract: The aim of this study was to compare the outcome of intracytoplasmic sperm injection (ICSI) and embryo transfer between couples with infertility due to male non-obstructive azoospermia (NOA) and obstructive azoospermia (OA). A retrospective analysis of 234 couples with azoospermia who were treated by ICSI and embryo transfer between January 2007 and October 2010 was performed. There were 61 couples in NOA group and 173 couples in OA group. Fertilization rates, pregnancy and clinical pregnancy rates were the main outcome measures. The number of retrieved mature oocytes, injected oocytes, metaphase II (MII) oocytes, two distinct pronuclei oocytes, cleavage embryos and embryos transferred was not significantly different between the groups. The fertilization rate was significantly lower in NOA group when compared to OA group (56.2 vs. 66.7%, respectively; p  = 0.013) and the pregnancy rate was significantly lower in NOA group than OA group (36.1 vs. 50.9%, respectively; p  = 0.046). The clinical pregnancy rates were not statistically different between the patients with NOA and OA azoospermia groups (24.6 vs. 36.4%, respectively; p  = 0.09). This study suggests that ICSI and embryo transfer together with testicular sperm extraction results in statistically significant lower fertilization and pregnancy rates in men with NOA when compared to men with OA.